ANALISA PENGARUH VARIASI BULBOUS BOW JENIS HIU MARTIL TERHADAP HAMBATAN KAPAL - Ade Brahma Marcelino Aplugi (JURNAL JALASENA, 2023)
Ship resistance is a topic that is still being discussed at this time, everyone who has knowledge in the field of shipping is competing to minimize the resistance that occur in the ship's hull. At this time there have been many innovations regarding hull design that can evaluate ship resistance, for example bulbous bows, stern flaps, skeg and so on. Resistance that are too large will be very detrimental, starting from fuel consumption, engine durability and ship building structures. The design concept of this bulbous bow is taken from the shape of a living creature or what is usually called biomimetic engineering, this bulbous bow is shaped like the head of a hammerhead shark which has a mouth that extends horizontally. The results of the bulbous bow design concept are expected to reduce ship resistance.